Primary primitive neuroectodermal tumor of the bladder: A case report - Erdogan, Bahattin; Cetin, Kismet Civi (Indian Journal of Case Reports, 2024)
A primitive neuroectodermal tumor (PNET) is part of the Ewing sarcoma family of tumors. PNET of the urinary bladder is extremely rare. In this paper, we describe the case of a 42-year-old man with a PNET of the bladder. He presented with dysuria and microscopic hematuria. Pelvic computed tomography showed a mass in the urinary bladder. He had undergone transurethral resection of the tumor. Histology of tumor biopsies showed a highly cellular, focally necrotic small round-cell tumor with numerous mitoses and occasional rosette-like structures. Strong CD99 and vimentin expression and focal reactivity to CD117 (c-kit) were observed in tumor cells. The patient did not accept surgery and chemotherapy. He is alive and well with no evidence of disease 4 years after the surgery.